2014
DOI: 10.1007/s12282-014-0575-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the progesterone receptor status in Ki67-high and -low Luminal B-like HER2-negative breast cancers

Abstract: Our results show the possibility that PgR status has some influence on the prognosis for Luminal HER2-negative breast cancers. Therefore, attention should be paid to the PgR status as well as Ki-67.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The associations between lipoproteins and breast cancer development and prognosis may vary by type of lipoproteins, as we observed a positive association between the larger HDLs and PgR expression in breast tumors, but no associations between the smaller and more dense HDL4 and PgR expression. Recently, PgR expression < 20 % has been associated with poor prognosis [ 36 , 47 , 48 ], and patients initially diagnosed with PgR+ breast cancer had a worse outcome if recurrence of disease was PgR− [ 49 ]. Moreover, the TransAttack study showed that the lowest PgR percentage quartile had an unfavourable prognosis as compared to the highest quartile [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The associations between lipoproteins and breast cancer development and prognosis may vary by type of lipoproteins, as we observed a positive association between the larger HDLs and PgR expression in breast tumors, but no associations between the smaller and more dense HDL4 and PgR expression. Recently, PgR expression < 20 % has been associated with poor prognosis [ 36 , 47 , 48 ], and patients initially diagnosed with PgR+ breast cancer had a worse outcome if recurrence of disease was PgR− [ 49 ]. Moreover, the TransAttack study showed that the lowest PgR percentage quartile had an unfavourable prognosis as compared to the highest quartile [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently in studies that included women with luminal tumors, it was observed a positive association between the Ki‐67 index and the PR expression in relations to overall disease‐free survival and other clinical outcomes; characterizing a better prognosis group between luminal tumors . These data reinforce that constant molecular subclassification may contribute to an even better therapeutical approach, as well as a better understanding of clinical outcomes associated with each breast cancer tumoral phenotype.…”
Section: Discussionmentioning
confidence: 80%
“…Especially, the low PR expression has had a high correlation with poor prognosis in postmenopausal patients 11) . PRlow or negative luminal B-like breast cancer showed significantly higher histological grade than that of PR-high luminal B-like breast cancer 12) . In our study, nuclear grade and Ki-67 labeling index were not significant different between PR+ group and PR− group, but showed tendency to higher nuclear grade and Ki-67 labeling index in PR− group.…”
Section: Discussionmentioning
confidence: 81%